Evidence or no evidence for essential fatty acids in the treatment of autism spectrum disorders? - Pancheva, Rouzha Zlatanova; Nikolova, Silviya; Serbezova, Asena; Zaykova, Krassimira; Zhelyazkova, Desislava; Dimitrov, Lubomir (Frontiers in Nutrition, 2023)
Autism spectrum disorders (ASDs) are a group of neurodevelopmental disorders that affect social communication, behavior, and sensory processing in which PUFA are considered important. This mini review article aims to investigate the current evidence regarding the use of essential fatty acids (EFAs) in the treatment of autism spectrum disorders (ASDs). The study examines various research studies, related to EFAs, their benefits, and their role in ASD treatment. The article focuses on exploring the potential mechanisms underlying the effects of EFAs in ASD, including their antiinflammatory, antioxidant, and neuroprotective properties. Furthermore, the study discusses limitations and challenges associated with the use of EFAs in ASD treatment, including variability in dosage, and duration of treatment. The results of this review indicate that while some studies suggest a positive effect of EFAs on ASD symptoms, there is currently insufficient evidence to support their routine use as a standalone treatment for ASD. The need for further research to better understand the potential benefits and limitations of EFAs in ASD treatment is highlighted.